(untitled) (Bulletin KNOB, 2000)
Fir (Albies alba) can be dendrochronologically analyzed and dated without problems. This applies for wood from monumental buildings as well as for wood from archaeological excavations. Sometimes a few to possibly some ten years of difference occurs between the dating of fir and oak from the same context, as well as between spread datings of fir from one context. This may point to a longer period of transport or storage of the fir used in the Netherlands, in comparison with the usually freshly processed oak. Spruce is only rarely found in monumental buildings, but was used in combination with fir in the period around 1300. However, the few samples analyzed could not be dated. Pine was notably used in monumental buildings from the I7th century onwards. Most of the pine found could not be dated, because few samples were available per building and they were not comparable in number of annual rings, annual ring structure and origin. Consequently. the chance of a dendrochronological dating of pine is small.